The maintenance of the productivity and value of farmland in savanna through the effective management of bush encroachment: Ecological considerations - Smit, Nico (Acta Structilia, 2009)
Due to bush encroachment the grazing capacity of large areas of the Southern African savanna has declined, often to such an extent that many previously economic livestock properties are now no longer economically viable. Causes of bush encroachment include the exclusion of occasional hot fires. the replacement of most of the indigenous browsers and grazers by domestic (largely grazing) livestock, the restriction of movement of herbivores by the erection of fences. poor grazing management practice and the provision of artificial watering points. Removal of some or all of the woody plants will normally result in an increase of grass production and thus also the grazing capacity. However, the results of woody plant removal may differ between vegetation types, with the outcome determined by both negative and positive responses to tree removal. In view of this it can be concluded that any bush control program (chemical, mechanical or biological) should focus on tree thinning rather than clearing of all woody plants. It is important for any land manager to realize that there is no quick solution to the problem of bush encroachment. Effective management of bush encroachment should not be considered a once-off event. but rather a longterm commitment.